Quesintuu and Umantuu: Sirens and Andean Memory - Orías, Paola Revilla (2012)
This research analyzes the polysemic meanings and proposes an alternative interpretation to certain representations of Sirens found in a variety of colonial materials in the Andean region, particularly in the lacustrine region. This interpretation is based on the identification of some little known indigenous referent on two fishlike female beings from the surroundings of Lake Titicaca, whose memory has being preserved and rearticulated for centuries with content levels underlying European representation.